Auditoría tributaria, aplicada a la empresa servicios logísticos integrados Coimpexa cía. ltda., ubicada en la ciudad de Quito, en la provincia de Pichincha, en el periodo comprendido entre el 1 de enero al 31 de diciembre de 2014 - Velásquez Tapia, Gloria Paulina (2016)
This research was conducted to Integrated Logistics Services Company Coimpexa Cia. Ltda, Located In Quito which presented non-conformity development in its tax declarations carried out once in a month, for that reason there was a necessity to implement a tax audit during January 1st to December 31st ,2014 in order to evaluate whether their activities are being developed according to the planned objectives inside the company in order to achieve the tax obligations, which was applied deductive and inductive methods that allowed obtaining authentic information of the company staff and could find the following shortcomings such as: there is no appropriate internal control, the company didn’t give training to their employees, there is a bad digitalization to Value-Added Tax (VAT) and withholding tax returns….